2010
DOI: 10.1021/ja910500a
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Ligands Facilitate Bimetallic O2Homolysis at Five-Coordinate Oxorhenium(V) Centers

Abstract: Five-coordinate oxorhenium(V) anions with redox-active catecholate and amidophenolate ligands are shown to effect clean bimetallic cleavage of O(2) to give dioxorhenium(VII) products. A structural homologue with redox-inert oxalate ligands does not react with O(2). Redox-active ligands lower the kinetic barrier to bimetallic O(2) homolysis at five-coordinate oxorhenium(V) by facilitating formation and stabilization of intermediate O(2) adducts. O(2) activation occurs by two sequential Re-O bond forming reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
94
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 107 publications
8
94
0
Order By: Relevance
“…[5][6][7][8][9][10][11]23 The phenoxyl/phenolate redox couple is unexpectedly irreversible, in contrast with what is commonly observed in Ni(II) salen complexes involving sterically hindered phenolates. 23 This behaviour most likely results the higher lability of the proton of the Cβ (C7 in Fig.…”
Section: Electrochemistrymentioning
confidence: 99%
“…[5][6][7][8][9][10][11]23 The phenoxyl/phenolate redox couple is unexpectedly irreversible, in contrast with what is commonly observed in Ni(II) salen complexes involving sterically hindered phenolates. 23 This behaviour most likely results the higher lability of the proton of the Cβ (C7 in Fig.…”
Section: Electrochemistrymentioning
confidence: 99%
“…21 It was also reported that redox-active ligands promote air oxidation of an oxorhenium-(V) complex to a dioxorhenium(VII) product. 22 In the case of photoactive iron(III) or manganese(III) complexes such as porphyrin complexes, the photoirradiation was employed for O 2 activation. 23−28 The present study describes another attractive route of O 2 activation, in which aqueous alkaline solution is employed for O 2 activation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Neese and co-workers applied Density Functional Theory (DFT) and ab initio methods for examining various trends in the experimental spectra of transition metal-complexes involving noninnocent ligands, 32 and for exploring systems of bioinorganic interest. 33,39 Recent experimental studies on the oxidation catalysis by the complex [Re V (O)(cat) 2 ] − with redox-active catecholate ligands showed 12,40 41 oxo−molybdenum, 42,43 and oxo− rhenium). 44 The characterization of the redox-active catecholate as electron-reservoir for O 2 homolysis was supplemented by computational studies.…”
Section: Introductionmentioning
confidence: 99%
“…44 The characterization of the redox-active catecholate as electron-reservoir for O 2 homolysis was supplemented by computational studies. 40 Yet, several mechanistic details remained unclear, especially regarding the kinetics: (1) How does the trans−cis isomerization occur in the initial phase? (2) What is the role of O 2 during this isomerization?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation